Crypto assets as a threat to financial market stability - Heike Joebges; Hansjörg Herr; Christian Kellermann (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2024)
Crypto assets' partial money-like use promotes toxic developments in the financial system. Even though crypto assets might be regarded as close substitutes to traditional money, we show that they lack important functions of money. Traditional fiat money requires several interacting institutions to stabilize its value and regulate its use. In our analysis, we elaborate on the risks associated with the difficulty of setting up regulatory institutions in the crypto sphere and the likelihood of periods of high volatility as well as their repercussions on the traditional financial system due to reciprocal integration. The shift of banking functions into the unregulated area of decentralized finance triggers a new quality of instability in the global financial system with an increasing probability of effects on the real economy. Regulation of crypto assets remains an urgent issue.
Keywords: E42; G01; G23; 330; crypto assets; Bitcoin; stablecoins; financial crisis